PENERAPAN PENDEKATAN SAINTIFIK DENGAN MULTIMEDIA UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA MATERI PERISTIWA DAN TOKOH PROKLAMASI KEMERDEKAAN INDONESIA BAGI SISWA KELAS V SDN 1 PEJAGOAN TAHUN 2015/2016 - Puspita, Intan Ade (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Scientific Approach Using Multimedia in Improving Social Science Learning about the Event and Hero of the Declaration of Indonesian Independence for the Fifth Grade Students of SD Negeri 1 Pejagoan in the Academic Year of 2015/2016. The objectives of this research is to improve social science learning outcomes. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Subjects of the research were the fifth grade students of SD Negeri 1 Pejagoan in the academic year of 2015/2016 totaling 28 students. Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. Techniques of collecting data were test and non-test. Source of data were derived from students, teacher, and document. The results of this research showed that: the application of scientific approach using multimedia can improve social science learning outcomes about the event and hero of the declaration of indonesian independence with minimum completeness criteria of more than 75 in the first cycle 69.04%, in the second cycle 81.66%, and in the third cycle 84.59%. Keywords: scientific approach, multimedia, learning outcomes, social scienceAbstrak: Penerapan Pendekatan Saintifik dengan Multimedia untuk Meningkatkan Hasil Belajar IPS Siswa Materi Peristiwa Dan Tokoh Proklamasi Kemerdekaan Indonesia bagi Siswa Kelas V SDN 1 Pejagoan Tahun 2015/2016. Tujuan penelitian ini untuk meningkatkan hasil belajar IPS. Penelitian ini merupakan Penelitian Tindakan Kelas Kolaboratif dilakukan selama 3 siklus. Subjek penelitian ini adalah siswa kelas V SDN 1 Pejagoan tahun ajaran 2015/2016 berjumlah 28 siswa. Validasi data menggunakan teknik triangulasi teknik dan triangulasi sumber. Teknik pengumpulan data yang digunakan yaitu tes dan non-tes. Sumber data dalam penelitian ini terdiri dari siswa, guru, dan dokumen. Hasil penelitian menunjukkan bahwa penerapan pendekatan saintifik dengan multimedia dapat meningkatkan hasil belajar IPS tentang peristiwa dan tokoh proklamasi kemerdekaan Indonesia dengan KKM = 75. Hal ini terbukti dengan adanya peningkatan pada tiap siklusnya, yaitu pada siklus I sebesar 69,04, siklus II 81,66, dan siklus III 84,59. Kata Kunci: pendekatan saintifik, multimedia, hasil belajar IPS